2005
DOI: 10.1038/sj.leu.2403894
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeeper pathways and cellular background in the pathogenesis and therapy of AML

Abstract: Acute myelogenous leukemia (AML) is characterized by the accumulation of immature cells due to disturbed differentiation and proliferation of the myeloid lineage. Genetic alterations affecting transcription factors and receptor tyrosine kinases have been identified in AML and causally linked to the disease. The goal of this review is to address the role of the different genetic alterations in self-renewal and proliferation and to discuss the cellular background in which these events occur during the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 94 publications
0
7
0
1
Order By: Relevance
“…It has been demonstrated that DC are not activated in human cancers and that their function is compromised by the tumor (1)(2)(3)(4)(5)(6). Several lines of evidence indicate that the ability of tumors to affect DC maturation and differentiation may result in a generalized failure of the host to mount an effective antitumor response.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…It has been demonstrated that DC are not activated in human cancers and that their function is compromised by the tumor (1)(2)(3)(4)(5)(6). Several lines of evidence indicate that the ability of tumors to affect DC maturation and differentiation may result in a generalized failure of the host to mount an effective antitumor response.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…Changes in transcriptional control of hematopoietic cells and mutations involving different proto-oncogenes or tumor suppressors account for the deregulation of normal myelopoiesis (3). Such changes ultimately result in activation of cellular pathways that mediate signals that promote cell growth and/or maintain survival, leading to leukemogenesis (4, 5). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, changes in the transcriptional control in hematopoietic cells modify the arrays of signal transduction effectors available for growth factor receptors, whereas activating mutations in signal transduction molecules induce alterations in the activity and expression of several transcription factors that are essential for normal myeloid differentiation. 13,14 The phosphoinositide 3-kinase (PI3K)/Akt signaling network is crucial to widely divergent physiological processes that include cell cycle progression, differentiation, transcription, translation and apoptosis. 15,16 It is targeted by genomic aberrations including amplification, mutation and rearrangement more frequently than any other pathway in human cancer, with the possible exception of the p53 and retinoblastoma pathways.…”
Section: Introductionmentioning
confidence: 99%